Pengaruh Model Pembelajaran Jurisprudential Inquiry Terhadap Kemampuan Menulis Teks Editorial Siswa Kelas XII SMA Negeri 2 Tanjung Morawa - Kristina Damai Yanti Simorangkir; Syamsul Arif (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research was carried out with the aim of finding out the effect of the jurisprudential inquiry learning model on the ability to write editorial texts. The population of this study was all class XII of SMA Negeri 2 Tanjung Morawa, totaling 7 classes. The sample was taken with no more than 40 students per class, so class XII Science 2 had 35 students as the experimental class and class XII Science had 34 students as the control class. The instrument used is a test of the ability to write editorial texts. Data measurements were carried out twice, namely measurements in the experimental class and the control class. From the data processing, it shows that the ability to write editorial texts in class .05, standard deviation 13.15. This can be seen in the normality test, the jurisprudential inquiry learning model is Lcount < Ltable namely 0.205 < 0.337. Then in the conventional learning model Lcount < Ltable, namely 0.192 < 0.319. Because Lcount is smaller than Ltable, the two data above are said to be normally distributed. Likewise, the results of the data homogeneity test are Fcount < Ftable , namely 0.54 < 0.56, so the data comes from a homogeneous population. After testing normality and homogeneity, hypothesis testing was carried out, obtained tcount > ttable with hypothesis test results of 6.35 and significance a = 0.05 and df = 35+34-2 = 67, so at the 5% level we obtained ttable = 1.99601. Thus it can be concluded that tcount > ttable , namely 6.35 > 1.99601, so the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This proves that the jurisprudential inquiry learning model is more influential in improving the editorial text writing skills of class XII students at SMA Negeri 2 Tanjung Morawa.